2015
DOI: 10.1016/j.compstruct.2015.08.035
|View full text |Cite
|
Sign up to set email alerts
|

The oblique impact response of composite sandwich plates

Abstract: This is a postprint version of the following published document:Iváñez, I.; Moure, M. M.; García-Castillo, S. K.; Sánchez-Sáez, S. (2015). The oblique impact response of composite sandwich plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…Figure 19 shows the C-scan images for different oblique angles and impact energies. The failure profile on the front side was different among normal and oblique impact [296]. Under normal impact, fiber failure induced by shearing was noticed on the front side.…”
Section: Angle Of Obliquitymentioning
confidence: 91%
“…Figure 19 shows the C-scan images for different oblique angles and impact energies. The failure profile on the front side was different among normal and oblique impact [296]. Under normal impact, fiber failure induced by shearing was noticed on the front side.…”
Section: Angle Of Obliquitymentioning
confidence: 91%
“…Generally, for a better representation of the damage scenario, the composite skin and the core have to be modeled separately. This is all the more true when complex loading, like oblique impacts, are studied [9,10,11]. For the modeling of the woven composite skin, the representation scale varies from the homogenized skin to the representation of the bundles of fibers with solid elements [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the damage state and the impact response were independent of core thickness, which was tested with two different core thicknesses; 10 and 25 mm. The oblique impact response of sandwich composite having carbon/epoxy face sheets and Nomex honeycomb core was investigated in Iva´n˜ez et al [4]. It was found that the peak load and energy absorption increased with increasing impact energy and impact angle, while the contact time remained almost constant.…”
Section: Introductionmentioning
confidence: 99%